(untitled) (Docentes 2.0 Journal, 2021)
In the training processes, it is necessary to reinforce empathy, which is considered a fundamental aspect and sufficiently relevant to be considered for its evaluation in a specific way. The present research studied the effects of rigid quarantine on empathic capacity from a cognitive and affective approach, both in assessing the empathic process and in the interpretation of its four specific scales: adoption of perspectives, emotional understanding, empathic stress, and joy. In psychology, students are in the middle of their professional training within a private university. The study was based on the quantitative approach, which contemplates a contemporary transactional descriptive research design and uses a discretionary non-probabilistic sample. For the present investigation, the students who were recurrent in their participation in virtual classes were selected. The information collection was through applications of the Cognitive and Affective Empathy Test; the study was carried out during rigid pandemic quarantine by Covid-19. The items were transcribed into an electronic form, using Microsoft Forms tools, after contextualizing and adapting them to the Bolivian context. It identified that the pandemic situation affected the empathic characteristics of the students, mainly: the ability to put one in the other’s shoes, as well as the ability to share the positive emotions of another person.